Manajemen Musyawarah Kerja Kepala Sekolah (MKKS) SMP dalam Pengembangan Keprofesian Berkelanjutan Pada Dinas Pendidikan Kabupaten Sinjai - Muallim Muallim; Chalid Imran Musa; Ansar Ansar (Journal on Education, 2023)
This study examines the management of junior high school principals' work deliberations (MKKS) in continuing professional development at the Sinjai District Education Office. The purpose of this research is to find out the description of planning, implementation, supervision as well as the supporting and inhibiting factors of MKKS activities in sustainable professional development. This study used descriptive qualitative method. Research data obtained by using interviews, observation and documentation. Data analysis techniques namely data reduction, data presentation and drawing conclusions. Checking the validity of the data using triangulation techniques. The results of the research show that: (1) work program planning is carried out by analyzing the needs of continuing professional development (AKPKB) and determining PKB priorities in the work program, formulating the results to be achieved, and preparing sources and uses of funding; (2) the implementation of the work program is carried out in accordance with established procedures by taking into account the three elements of PKB, namely self-development, innovative work and scientific publications, but the implementation of the MKKS program seems monotonous and the PKB program is almost the same every year and lacks PKB implementation on elements of scientific publications; (3) supervision in MKKS includes supervision at the initial stage of planning, supervision of program implementation, supervision at the final stage of evaluating the program and financial supervision whose time is conditioned; (4) supporting factors, namely good collaboration of members due to the need to increase the same competence, support from educational institutions and independent funding, while inhibiting factors, namely being vulnerable to age which results in differences in understanding, difficulties in developing the mindset of MKKS members who are about to retire regarding PKB and meetings the discussion did not bring up new ideas or ideas for program improvement.